遊離腸骨移植の術後感染に自動洗浄機能を有した局所陰圧閉鎖療法が奏効した1例 - 橋本, 憲一郎; 池邉, 哲郎; 吉住, 潤子; 宮原, 慧; 横尾, 嘉宣; 平木, 昭光 (日本口腔外科学会雑誌, 2021)
Negative pressure wound therapy with instillation and dwelling (NPWTi-d), which can bring about automatic perfusion inside a wound, is becoming one of the standard treatment options for wound healing in all surgical fields. There are few reports regarding NPWTi-d in the field of oral and maxillofacial surgery. We report a case of post-operative infection of an iliac bone graft which was successfully treated with NPWTi-d. The patient was a 62-year-old man. We performed segmental resection of the mandible and modified radical neck dissection, followed by reconstruction with a plate and pectoralis major musculocutaneous flap for a lower gingival squamous cell carcinoma. One and a half years later, secondary reconstruction was performed using iliac bone. On the 13th day after surgery, an infection was found in the drain insertion site. After drainage NPWTi-d was commenced the following day and continued for 13 days. The abscess disappeared and the drainage wound was closed. However, on the same day a new abscess was found in the submandibular region anterior to the previous lesion and NPWTi-d was performed again for 15 days. Finally, the wound completely healed and the patient was discharged 48 days after surgery. Seven months after surgery, no infection has been observed in the grafted bone.